Tokoh Amelia Sebagai Teladan untuk Siswa Perempuan Pendidikan Dasar: Kajian Literasi Moral dalam Novel Amelia Karya Tere Liye - Idris, Akhmad; Darni, Darni (Efektor, 2019)
Education holds a central role in the formation of the character's protégé. Through educational institutions are expected to take shape a child's intelligent and moral. Then, how if the institution was only able to give birth to a child who is smart, but not moral? This occurs because of less awareness of moral literacy. Literature as a means of teaching at the same time, the entertainer is expected to be a breakthrough to form a generation of moral literate. Amelia’s character in novel Amelia by Tere Liye can be used as a role model for female students in elementary education.